An examination of the effect of autumn closing date on over-winter herbage production and spring yield - C. Looney; D. Hennessy; A. Wingler; A. Claffey; M. Egan (Irish Journal of Agricultural and Food Research, 2021)
Altering autumn management affects the herbage mass available in spring. An experiment was established to determine the effect of five autumn closing dates (CDs) on herbage production, herbage quality, leaf, stem and dead proportions and tiller density over winter. In the study 50% of the herbage available in spring was accounted for by autumn CD. Each 1 d extra a sward was closed from 25 September to 9 December increased herbage mass by 16 kg DM/ha in spring. Swards closed earlier (25 September–26 October) had consistently higher herbage masses in spring (1,301 kg DM/ha) compared to swards closed later (11 November–9 December; 703 kg DM/ha). Later closed swards had greater herbage quality compared to earlier closed swards (organic matter digestibility = 852 and 825 g/kg DM, respectively) due to increased stem and dead material in the grazing horizon of earlier closed swards. There was no effect of autumn CD on sward quality in the subsequent defoliation in spring. However, following the initial spring grazing there was an effect of autumn CD on subsequent grass growth rates; swards closed in October had a lower growth rate (33 kg DM/ha per day) compared to swards closed in November and early December (49 kg DM/ha per day). Results indicate that earlier autumn closing is beneficial to meet high-feed demand in spring but can affect sward quality and growth rates in spring.